Nursing interventions to empower the family caregiver of person with lower limb amputation: scoping review - Diana Fonseca Rodrigues; Fabiana Sofia Ferreira Machado Castanheira; António Luís Rodrigues Faria de Carvalho; Cristina Maria Correia Barroso Pinto (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to map nursing interventions that empower the Family caregiver of the person with lower limb amputation for is role. Methods: scoping review guided by Joanna Briggs Institute methodology conducted in different databases (including gray literature). Results: six studies published between 2009 and 2021 were included. Interventions of counselling and support for patients and family; peer support interventions performed by a certified pair; involvement of caregivers or family members in support groups; and key interventions for patient and family caregiver psychological balance. Two studies discussed the importance of caregiver and amputee training and development of coping skills. Another study recommended Interventions of informative support for caregivers regarding care for the amputee and adaptation to home. Conclusions: results of this review allow the identification of recommendations (guidelines) for practice and recommendations/suggestions for interventions according with identified needs of family caregivers of patients with lower limb amputation.